Narrating Teacher Commitment: Exploring Organizational Citizenship Behavior through Transformational Leadership, Resilience, and Work Engagement in Indonesian Schools - Ida Solowati; Ghufron Abdullah; Qristin Violinda; Amel Baussaidi (Yayasan Adra Karima Hubbi, 2026)
Background. Organizational Citizenship Behavior (OCB) of teachers is crucial for enhancing school effectiveness, collaboration, and overall educational quality, as it reflects voluntary behaviors beyond formal job requirements. However, OCB is influenced by various organizational and individual factors, including leadership style, psychological resilience, and work engagement. Purpose. This study aimed to analyze the influence of transformational leadership, teacher resilience, and work engagement on Organizational Citizenship Behavior among teachers of State Junior High Schools in North Pekalongan District, Pekalongan City. Method. A quantitative approach with a survey design was employed. The study involved 115 teachers selected as respondents from the population of public junior high school teachers in the district. Data were collected using structured questionnaires that had been tested for validity and reliability. The data were analyzed using descriptive statistics and multiple linear regression to examine both partial and simultaneous effects of the independent variables on OCB. Results. The findings revealed that transformational leadership, teacher resilience, and work engagement each had a positive and significant effect on teachers’ OCB. Transformational leadership was identified as the most dominant predictor, followed by teacher resilience and work engagement. Simultaneously, the three variables explained a substantial proportion of variance in OCB, indicating that both organizational leadership and psychological factors play important roles in shaping teachers’ extra-role behaviors. Conclusion. Improving teachers’ OCB requires an integrated strategy that strengthens transformational leadership practices, enhances teacher resilience, and promotes higher work engagement. These results highlight the strategic importance of effective leadership and teacher well-being in fostering organizational effectiveness in educational institutions.